Manfaat Pranayama Yoga Untuk Mengurangi Kecemasan Pada Ibu Nifas di PMB Jaba Denpasar - Kadek Sri Ariyanti; Siti Zakiah; Cokorda Istri Mita Pemayun; I Nyoman Dharma Wisnawa (Jurnal Yoga dan Kesehatan, 2023)
The postpartum period is a transitional period in which physical and psychological changes occur. Postpartum depression is a psychological disorder that is often found. Postpartum depression is experienced by around 10‒15% of women, both for the first time and for the next. Pranayama yoga is one of the exercises that can relieve psychological discomfort in postpartum mothers. This study aims to determine the effectiveness of pranayama yoga to reduce anxiety in postpartum mothers. The research design used is qualitative with a case study approach. The informants in this study were 10 postpartum mothers at PMB Jaba Denpasar in December 2022 - January 2023. Data analysis was carried out by triangulation, where the key informants in this study were five husbands and midwives. The results showed that postnatal yoga can reduce anxiety in postpartum mothers, because it provides various benefits including: 1) reducing shoulder and neck muscle tension; 2) calm the mind and reduce stress; 3) improve sleep quality; 4) Increase milk production. Pranayama yoga practice should be given to postpartum mothers as an effort to improve the physical and psychological health of postpartum mothers.